The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1093/ofid/ofy304
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Infective Endocarditis in Persons Who Inject Drugs: “Take Another Little Piece of my Heart”*

Abstract: BackgroundInjection drug use (IDU) is a major risk factor for infective endocarditis (IE). Few data exist on repeat IE (rIE) in persons who inject drugs (PWID).MethodsPatients ≥18 years old seen at Wake Forest Baptist Medical Center from 2004 to 2017 who met Duke criteria for IE and who self-reported IDU in the 3 months before admission were identified. The subset of PWID who developed rIE, defined as another episode of IE at least 10 weeks after diagnosis of the first episode, was then reviewed.ResultsOf the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…The rate of recurrent endocarditis among PWID in our cohort was 32%, with 68 patients experiencing a second episode. This is higher than rates that have previously been reported in non–drug user populations (which range from 2.4% to 10.9%) [26] but is similar to a cohort of PWID from the 1970s where the recurrence rate was 41% [27] and a more contemporary population in North Carolina where the recurrence rate was 25.3% in PWID [9]. It remains unclear whether any clinical factors increase the likelihood of experiencing a second episode of endocarditis, beyond continued injection drug use.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The rate of recurrent endocarditis among PWID in our cohort was 32%, with 68 patients experiencing a second episode. This is higher than rates that have previously been reported in non–drug user populations (which range from 2.4% to 10.9%) [26] but is similar to a cohort of PWID from the 1970s where the recurrence rate was 41% [27] and a more contemporary population in North Carolina where the recurrence rate was 25.3% in PWID [9]. It remains unclear whether any clinical factors increase the likelihood of experiencing a second episode of endocarditis, beyond continued injection drug use.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, the risk of recurrent endocarditis in PWID has been inconsistent. It has been shown that repeat endocarditis is associated with injection drug use [9, 25]; however, older studies before the recent opioid crisis did not note an association of recurrent endocarditis with injection drug use [17]. We present the largest case series of recurrent endocarditis among PWID to date.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…There has been very little data assessing the detailed injection practices associated with developing IE. The literature primarily studies the clinical and epidemiological characteristics of PWID developing IE [3,5,7,26,27]. Some studies assessing injection practices of PWID are in relation to the development of skin and soft tissue infections [28] or infections in general [14,20,29].…”
Section: Discussionmentioning
confidence: 99%